(untitled) (Third Sector Social Economic Review, 2019)
Communication technologies have brought about differences and changes in social habits, cultures, and forms of communication. The communication of the individual with his / her environment and with the world is often realized with information technologies. Moving away from traditional communication and communicating through social networks has brought about social alienation. Individuals are sliding into isolation due to changes in their communication styles and social lives. Social media detaches individuals from their environment and leads to the development of social contacts without emotional elements. Social media communication does not allow the satisfaction provided by the face to face communication where emotional satisfaction is experienced. This situation brings along many problems such as asocialization, self-alienation and so on in the individual and social life. This study aims to analyze the communicative reflections of social media, one of the developing communication technologies, in social life in the context of communication satisfaction.